Evolution and significance of clay minerals in the Esna Shale Formation at Dababiya area, Luxor, Egypt - A. El-Shater; A.M. Mansour; M.R. Osman; Ahmed A. Abd El Ghany; A. Abd El-Samee (Egyptian Journal of Petroleum)
The Esna Shale Formation is broadly distributed in Egypt and one of the most of its important clay deposits. These deposits in the Dababiya area, Luxor region were subjected to intensive laboratory investigations (XRD, IR, and SEM analyses). The bulk and clay mineralogy of this formation varies from one layer to the next and comprises the phyllosilicates, calcite as principal minerals with remarkable amounts of quartz, feldspars dolomites, and anhydrite. Fluorapatite, pyrite, schaurteite, despujolsite, goethite, and halite are present in some beds but minor quantities. The clay mineralogy consists of smectite (41%), sepiolite-palygorskite (28%), illite (13%), smectite/illite mixed layers (13%), and kaolinite (6%). Smectite was differentiated into three species: nontronite (21%), Na-and Ca-montmorillonites (13%), and beidellite (8%). Smectites are dioctahedral with a typical fully turbostratic stacking mode and crystallite sizes varying from 2 to 3 nm. The detrital input is the dominant aspect responsible for distributing clay minerals in these marine sediments. The presence of shallow Paleogene constrained basins between arose land areas in Egypt, favorable to the neoformation of palygorskite and sepiolite, It indicates that most of the fibrous clay minerals present in this part of the Tethys could have formed in these coastal basins and that their presence is an indication of aridity. By transcending global sea level that occurred at the end of the Paleocene, the nonappearance of kaolinite at the Dababiya area (southern Egypt) and its richness at the Wadi Nukhul Section (Sinai, Egypt) no relationship is shown between differences in kaolinite abundance and sea level fluctuations during this period. Six units of clay mineral species were distinguished throughout this formation reflecting their evolution.